229k views
2 votes
What's the answer? help asap
plssssss
Please show full explanation! ​

What's the answer? help asap plssssss Please show full explanation! ​-example-1

1 Answer

5 votes

Answer:


\huge\boxed{Answer\hookleftarrow}

Given,


3x - 2y = 5


xy = - 2

Now,


(3x - 2y) {}^(2) = (5) {}^(2) \\

Use the algebraic identity (a - b)² = a² - 2ab + b²


(3x - 2y) {}^(2) = (5) {}^(2) \\ 3x {}^(2) - 2 * 3x * 2y + 2y {}^(2) = 5 {}^(2) \\ 9 {x}^(2) - 12xy + 4y {}^(2) = 25 \\9x {}^(2) + 4y {}^(2) = 25 + 12xy \\ 9x {}^(2) + 4 {y}^(2) - 1 = 24 + 12xy

So, the value of 9x² + 4y² - 1 is 24 + 12xy

Now,

xy = - 2

So, 12xy = 12 × - 2 = - 24

•°• 24 + 12xy

= 24 + (-24)

= 24 - 24

= 0

The value of 9x² + 4y² - 1 is 0.

ʰᵒᵖᵉ ⁱᵗ ʰᵉˡᵖˢ

# ꧁❣ RainbowSalt2²2² ࿐

User Karacas
by
8.1k points